URGENSI SIGHAT TAKLIK SEBAGAI UPAYA MENCEGAH DISHARMONI DALAM KELUARGA - Padlianor (LPPM STAI Muhammadiyah Probolinggo, 2025)
Islamic marriage aims to establish a harmonious family; however, the high rates of divorce and Domestic Violence (KDRT) in Indonesia indicate the frequent neglect of wives’ rights. Sighat Taklik, a husband’s conditional pronouncement of divorce post-marriage contract (akad nikah), is an instrument within Indonesian Islamic law to protect wives’ rights. However, husbands’ understanding of its consequences is often minimal. This research aims to examine the urgency of sighat taklik in preventing family disharmony, analyze its concept, legal basis, and implications, and propose solutions to enhance its effectiveness. The method employed is descriptive-analytical, based on a literature review of the Al-Qur’an, Hadith, Compilation of Islamic Law (KHI), Marriage Law, journals, and statistical data. The findings indicate that sighat taklik is a declaration of divorce contingent upon specific conditions such as abandoning the wife, failing to provide maintenance, inflicting physical harm, or neglecting the wife, the violation of which grants the wife the right to file for divorce by paying iwad (compensation). Its legal foundation is derived from Articles 45-46 of the KHI and Surah An-Nisa verse 128. Its urgency lies in protecting wives’ rights and serving as a reminder of spousal responsibilities, although husbands’ lack of understanding hinders its effectiveness. Proposed solutions include pre-marital socialization, educational modules, religious studies, and public campaigns to increase awareness..